Determinants Of Intention In Using The Village Financial System (Siskeudes) Using The Theory Of Planned Behavior (Tpb) Approach In Mojokerto District - Rochman, Yusuf Fatkhur; Roekhudin; Aulia Fuad Rahman (The International Journal of Accounting and Business Society, 2024)
Purpose: This study aims to determine and analyze the effect of attitudes, subjective norms, and behavioral control on intention to use the village financial system (SISKEUDES), with intention as an intervening variable. Design/methodology/approach: This study uses a quantitative approach, with the population being all IT-based SISKEUDES Operators (online) Village Government in Mojokerto Regency. The data analysis technique uses path analysis with the calculation process using the SPSS (Statistical Package for the Social Sciences) released 24 programs. Findings: The analysis's results show a significant positive influence of attitudes, subjective norms, and behavioral control on intention to use the village financial system (SISKEUDES). Intention is proven to be an intervening variable in the influence of attitudes, subjective norms, and behavioral control on behavior using the village financial system (SISKEUDES). Practical implications: The Mojokerto District Government can plan before using the village financial system (SISKEUDES). These efforts ensure that the resource factors owned can support the village financial system (SISKEUDES). The planning can be done by providing training and technical guidance (Bimtek) to human resources in managing the village financial system (SISKEUDES). Originality and value: This study develops the Theory of Planned Behavior (TPB) by studying intention as an intervening variable in the influence of attitudes, subjective norms, and behavioral control on behavior. Keywords – Attitude, Subjective Norms, Behavioral Control, Intention and Behavior, Sistem Keuangan Desa (SISKEUDES).